Empathy Mediates the Relationship Between Motivations After Transgression and Forgiveness - Ma, Lin; Jiang, Yingjie (Frontiers in Psychology, 2020)
Previous studies found the associations between motivations after transgression and forgiveness in adults. However, less is known about the relationship between transgression-related motivations and forgiveness among adolescents and the potential mediating role of empathy. These questions were investigated among 445 Chinese adolescents using the Tendency to Forgive Scale, the Transgression-Related Interpersonal Motivations Inventory, and the Interpersonal Reactivity Index. The results found a negative relationship between avoidance and revenge motivation and forgiveness tendency, a positive association between benevolent motivation and forgiveness tendency. In addition, the study also revealed a partial mediating role of empathy regarding the effect of the transgression-related motivations on forgiveness tendency. These findings suggested that empathy play a vital role in the relationship between the transgression related motivations and forgiveness among adolescents.